Patient Factors and Preferences in Choosing Sleep Surgery for Obstructive Sleep Apnea: A Qualitative Study. (19th January 2023) - Ikeda, Allison K.; McShay, Crystina; Marsh, Robin; Saini, Shireen; Sardesai, Maya G.; Weaver, Edward M.; Boss, Emily F.
Abstract: Objective: There are several obstructive sleep apnea (OSA) treatment options available to patients, including surgery and less invasive therapies. Little is known about the factors that influence patient preferences for treatment. We aimed to understand factors influencing patient experience and decision making for undergoing sleep surgery. Study Design: Retrospective qualitative study. Setting: Tertiary sleep surgery clinic. Methods: We conducted semistructured interviews with adults who previously underwent any nasal and/or pharyngeal sleep surgery. We asked open‐ended questions about their decision‐making process within a preconceived thematic framework of chief OSA symptoms, expectations for recovery, and sources of information. The interviews were audio recorded and transcribed, and content was analyzed for defined, emergent, and prevalent themes. Results: Ten patients were interviewed from December 11, 2020 through January 29, 2021. Six patients underwent nasal surgery, 1 underwent pharyngeal surgery, and 3 underwent staged nasal and pharyngeal procedures. All patients were beyond the acute recovery phase. Reasons for pursuing surgical consultation varied from sleep apnea burden to external factors, such as recommendations from significant others. Duration of sleep surgery consideration varied from months to years. Major concerns about sleep surgery involved anesthesia and postoperative pain. External factors influencing patients' decisions to pursue sleep surgery included family and friend support. Postoperative outcomes of surgery included patient satisfaction with decision for surgery, given OSA improvements. Conclusion: Understanding patient factors that influence decision making for sleep surgery may guide clinicians in patient‐centered counseling that engages patients in decision making, aligning with clinical symptoms and patient preferences.